Correlation between the Activities of Daily Living of Stroke Patients in a Community Setting and Their Quality of Life - Kim, Kyung (The Society of Physical Therapy Science, 2014)
[Purpose] The present study aimed to determine the correlation between the activities of daily living and the quality of life (QOL) of patients with chronic stroke. [Subjects and Methods] The study subjects were 68 patients with stroke. Three questionnaires were distributed by visiting the subjects. [Results] All the items and total scores of the functional independence measure (FIM) showed a high correlation with the QOL total score. The relationship between the activities of daily living and the total QOL score showed a significant positive correlation. Among the FIM items, mobility and social cognition showed the most significant effects. The modified r(2) value was 0.67, mobility and social cognition explained approximately 67% of the change in the QOL. [Conclusion] The activities of daily living of the patients with chronic stroke and their QOL showed a high correlation. Among the FIM items, mobility (transfers) and social cognition had the largest effects on the total QOL score.